Shi'i Jurisprudence and Constitution - Boozari, A. author. aut Link
XII, 252 p.
Keywords: Focusing substantially on the relation between the concept of constitutionalism and Islamic Law in general and how such relation is specifically reflected in the Shiite jurisprudence, this volume explores the juristic origins of constitutionalism, especially in the context of 1905 Constitutional Revolution in Iran.